Three-Dimensional Poly-(ε-Caprolactone) Nanofibrous Scaffolds Promote the Maturation of Human Pluripotent Stem Cells-Induced Cardiomyocytes - Zhang, Mingming; Xu, Yuerong; Chen, Yan; Yan, Qinru; Li, Xiaoli; Ding, Lu; Wei, Ting; Zeng, Di (Frontiers in Cell and Developmental Biology, 2022)
Although pluripotent stem cell-derived cardiomyocytes (iPSC-CMs) have been proved to be a new platform for heart regeneration, the lack of maturity significantly hinders the clinic application. Recent researches indicate that the function of stem cell is associated with the nanoscale geometry/topography of the extracellular matrix (ECM). However, the effects of 3D nanofibrous scaffolds in maturation of iPSC-CMs still remain unclear. Thus, we explored the effects of restructuring iPSC-CMs in 3D nano-scaffolds on cell morphology, cardiac-specific structural protein, gap junction and calcium transient kinetics. Using the electrospinning technology, poly-(ε-caprolactone) (PCL) nanofibrous scaffold were constructed and iPSC-CMs were seeded into these forms. As expected, strong sarcolemmal remodeling processes and myofilament reorientation were observed in 3D nano-scaffolds culture, as well as more expression of cardiac mature proteins, such as β-MHC and MLC2v. The mature morphology of 3D-shaped iPSC-CMs leaded to enhanced calcium transient kinetics, with increased calcium peak transient amplitude and the maximum upstroke velocity (Vmax). The results revealed that the maturation of iPSC-CMs was enhanced by the electrospun 3D PCL nanofibrous scaffolds treatment. These findings also proposed a feasible strategy to improve the myocardium bioengineering by combining stem cells with scaffolds.